Evaluation of the topical gel and oral administration of Punica Granatum Var Pleniflora on oral mucositis induced by 5-Fluorouracil in golden hamsters - Seyede Pegah Hamidi; Omid Koohi-Hosseinabadi; Sepideh Khaksar; Ali Ghanbariasad; Amir Reza Dehghanian; Azizallah Dehghan; Zahra Haddadi; Roxana Gorgin; Mojtaba Farjam; Hiva Alipanah (BMC, 2023)
Abstract Background Oral mucositis (OM), an acute inflammation of the oral cavity, is a common complication in patients undergoing invasive myeloblastic chemotherapy or radiation therapy. 5-fluorouracil (5-FU) is one of the most effective therapeutic drugs, but one of the common side effects of 5-FU administration is OM. Unfortunately, no suitable treatment has been found, so far to control its side effects. Studies showed that herbal medicine like Punica granatum var pleniflora (PGP) has medicinal properties such as anti-inflammatory and antibacterial and can be an alternative for the treatment of fungal infection. Accordingly, we decided to investigate the therapeutic effect of PGP in the treatment of OM caused by 5-FU in golden hamsters. Methods Sixty male golden hamsters were divided into six main group. Chemotherapy with 5-FU at dose of 60 mg/kg was performed at a ten-day duration. Then, cheek pouches of the hamsters were scratched with an 18-gauge sterile needle to induce oral mucositis in animals. On the twelfth day, as a day of intensification of OM, treatment with PGP including topical gel with concentrations of 5% and 10% and oral administration of hydro-alcoholic extract with doses of 125 mg/kg and 250 mg/kg for three- and five-day therapeutic duration were separately started. Finally, samples of cheek pouches in hamsters were collected on 14th and 17th days and histopathologic score (HPS), malondialdehyde (MDA), and myeloperoxidase (MPO) levels were assayed. Results A significant (p < 0.05) decrease in histopathologic score was observed in G10%−, P125-treated groups in comparison to the Ctrl group. Our data showed that treatment with G10% is more potent than P125-treated group. In contrast, histopathologic score in G10%, P125, and P250 treated groups demonstrated almost similar values On the 17th day. However, the levels of MDA and MPO in the treatment groups were enhanced compared with control group (p < 0.05). Conclusions It is possible that PGP can play protective role in the healing of tissue damage caused by chemotherapy with 5-FU due to the presence of its natural compounds and antioxidant properties.